The Effect of Cancellation of Regional Regulations on Retribution Toward Regional Financial Regency In West Java - Huda, Uu Nurul (De Jure: Jurnal Hukum dan Syari'ah, 2020)
Abstract: Law no. 12 of 2011 concerning the Formation of Legislation Regulations has established provincial and regencies / city regional regulations in the hierarchy of laws and regulations as well as regional legal products. In order to explore regional financial resources, regencies / cities can issue regional regulations regarding regional user fees. However, the presence of local regulations on retribution in several regencies / cities often results in problems in the community because the presence of these regulations will add burden to the community concerned and / or conflict with higher policies or regulations. On this basis the government through the Ministry of Home Affairs conducted supervision and many canceled the regional regulation on retribution in various regions including regencies / city areas in West Java. This paper aims to analyze the authority and purpose of the cancellation of regional regulations and their effects on the regencies / city financial area in West Java. This study uses an empirical juridical approach with descriptive analysis in analyzing the research problems. The results of the study showed that the cancellation of the regulation on retribution was intended as a repressive effort by the central government so that the regions were not too far in making the regulation on retribution, the central government had the authority to conduct supervision and guidance by reviewing provincial and regencies / city regional regulations, in addition to judicial review by the Supreme Court. The existence of the cancellation of regional regulation on retribution has an effect on the loss of Regional Original Revenue (PAD) as a source of regional finance. The loss of retribution also affects the level of effectiveness and efficiency of local government administration, especially in aspects that are supported by the retribution budget.Keywords: retribution; regional regulations; law.Â Abstrak:UU No. 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan telah menetapkan peraturan daerah provinsi dan kabupaten/kota dalam hierarkhi peraturan perundang-undangan sekaligus sebagai produk hukum daerah. Dalam rangka menggali sumber keuangan daerah, kabupaten/kota dapat menerbitkan peraturan daerah mengenai retribusi daerah. Namun, hadirnya perda retribusi di beberapa kab/kota sering mengakibatkan persoalan di masyarakat karena hadirnya perda tersebut akan menambah beban bagi masyarakat yang berkepentingan dan/atau bertentangan dengan kebijakan atau aturan yang lebih tinggi. Atas dasar itulah pemerintah melalui Kementerian Dalam Negeri melakukan supervisi dan banyak membatalkan perda retribusi di berbagai daerah termasuk daerah kabupaten/kota di Jawa Barat. Tulisan ini bertujuan untuk menganalisis kewenangan dan tujuan pembatalan perda retribusi dan pengaruhnya terhadap keuangan daerah kabupaten / kota di Jawa Barat. Penelitian ini menggunakan pendekatan yuridis empiris dengan analisis deskriptif dalam menganalisis permasalahan penelitian tersebut. Hasil penelitian menunjukkan bahwa adanya pembatalan perda retribusi dimaksudkan sebagai upaya represif pemerintah pusat agar daerah tak kebablasan dalam membuat perda retribusi, pemerintah pusat memiliki kewenangan untuk melakukan pengawasan dan pembinaan dengan melakukan review terhadap peraturan daerah provinsi dan kab/kota, di samping judicial review oleh Mahkamah Agung. Adanya pembatalan peraturan daerah retribusi berpengaruh pada hilangnya Pendapatan Asli Daerah (PAD) sebagai salah satu sumber keuangan daerah. Hilangnya retribusi juga berpengaruh pada tingkat efektifitas dan efisiensi penyelenggaraan pemerintahan daerah, terlebih pada aspek yang ditunjang anggarannya oleh retribusi tersebut.Kata Kunci: retribusi; peraturan deaerah; hukum.